Results of Total Hip Replacement Surgery Using Short-Stem Spiron Prosthesis in Vietnamese Adults - Mai Duc Thuan; Nguyen Quoc Dung (Advances in Orthopedics)
Introduction. Total hip arthroplasty with traditional stem joints, although bringing many benefits to patients indicated for hip replacement, faces many difficulties in reoperations in young patients due to the limited lifespan of the artificial joint. Recently, the short-stem joint was introduced to help overcome this problem. This study aims to evaluate the results of short-stem implants for primary total hip arthroplasty in Vietnamese adults. Materials and Methods. The study design is retrospective longitudinal. The study subjects were 91 patients with aseptic necrosis of the femoral head who underwent short-shaft cementless total hip replacement surgery from February 2012 to December 2018. Outcomes that were assessed included implant survivorship, Harris hip scores, thigh pain, periprosthetic fracture, subsidence, proximal stress shielding, the prevalence of stem malalignment, and inappropriate implant sizing. Results. Our research group has 119 hips of 91 patients (28 patients had hip replacements on both sides), with the average follow-up time of 67.1 months. Seven cases of early joint loosening required replacing the traditional stem. The survival rate is 94.1%. The average Harris hip score 24 months after surgery was statistically significantly higher than before (92.00 ± 4.47 and 45.56 ± 3.22, respectively, p<0.001). The average leg length discrepancy between the two limbs before surgery was 9.5 ±mm and 24 months after surgery was 3.4 ± 2.9 mm. There were 12 cases (10.1%) of partial bone loss around the femoral stem; 12 cases of joint displacement of more than 2 mm, accounting for 10.1%; and 1 case of acetabular fracture, accounting for 0.8%. Conclusion. The Spiron short stem has certain advantages suitable for young patients, restoring the hip anatomy and significantly improving postoperative hip function. However, this is a complex technique that needs to be performed by experienced surgeons who have practiced for a long time. We encourage using the short-stem implant during primary total hip arthroplasty in Vietnamese adult patients.